Pengaruh Non Performing Loan (NPL) , BOPO dan Ukuran Perusahaan Terhadap Return On Assets (ROA) Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) - Nur Khamisah; Dhiona Ayu Nani; Izza Ashsifa (Universitas Teknokrat Indonesia, 2020)
The study entitled Analyzed Influencing Non-Performing Loan (NPL), BOPO and Size on Return On Assets in regional development banks Indonesia during period 2010 through 2013. This research is performed in order to test the influence of the variable Non-Performing Loan (NPL), BOPO and Firm Size toward Return on Assets (ROA) simultanously and partially. Obtained by amount sample as much 24 company banking company in Indonesia 2010-2013 period. The sample was selected using purposive sampling method. The data collected will be analyzed using multiple linear regression with and using SPSS 19 for Windows. The results showed that non-performing loan, BOPO and Size simultaneous effect on return on assets. The partially that non-performing loan ratio is partially negative but unsignificant effect on return on assets, BOPO significant and negative effect on return on assets and Size ratio is partially positive and unsignificant effect on return on assets